The Metabolic Basis of Immune Dysfunction Following Sepsis and Trauma - McBride, Margaret A.; Owen, Allison M.; Stothers, Cody L.; Hernandez, Antonio; Luan, Liming; Burelbach, Katherine R.; Patil, Tazeen K.; Bohannon, Julia K.; Sherwood, Edward R.; Patil, Naeem K. (Frontiers in Immunology, 2020)
Critically ill, severely injured and high-risk surgical patients are vulnerable to secondary infections during hospitalization and after hospital discharge. Studies show that the mitochondrial function and oxidative metabolism of monocytes and macrophages are impaired during sepsis. Alternatively, treatment with microbe-derived ligands, such as monophosphoryl lipid A (MPLA), peptidoglycan or β-glucan, that interact with toll-like receptors and other pattern recognition receptors on leukocytes induces a state of innate immune memory that confers broad-spectrum resistance to infection with common hospital-acquired pathogens. Priming of macrophages with MPLA, CPG oligodeoxynucleotides (CpG ODN) or β-glucan induces a macrophage metabolic phenotype characterized by mitochondrial biogenesis and increased oxidative metabolism in parallel with increased glycolysis, cell size and granularity, augmented phagocytosis, heightened respiratory burst functions and more effective killing of microbes. The mitochondrion is a bioenergetic organelle that not only contributes to energy supply, biosynthesis and cellular redox functions but serves as a platform for regulating innate immunological functions such as production of reactive oxygen species (ROS) and regulatory intermediates. This review will define current knowledge of leukocyte metabolic dysfunction during and after sepsis and trauma. We will further discuss therapeutic strategies that target leukocyte mitochondrial function and might have value in preventing or reversing sepsis- and trauma-induced immune dysfunction.